The Correlation between Calcium Intensity and Histopathological Changes in Brachial Plexus Nerve Injuries - Davis, John; O'Connor, Elizabeth; Zhang, Lin-Ling; Agresti, Michael; Matloub, Hani S.; Sanger, James; Jaradeh, Safwan S.; Yan, Ji-Geng (Journal of Reconstructive Microsurgery, 2013)
Background After nerve injury, an influx of calcium exceeds the homeostatic capacity, which damages peripheral nerves. Previous studies identified that following nerve crush, function improves as calcium levels normalize.Methods Electrophysiological analysis was performed to measure the compound muscle action potential of 15 patients' damaged nerves. These samples were evaluated for calcium level and also stained with a Luxol fast blue and neurofilament antibodies to evaluate the myelin sheath and neurofilaments of the nerves. Based on the Sunderland scale, we identified three exclusive types of peripheral nerve injury groups.Results There was a correlation between histopathological damage and calcium levels of 0.81 (p < 0.005). The average relative fluorescence units (RFUs) was 235.28 ± 19, which corresponds to 5.3 × 10−7 M of calcium, five times the normal value.Conclusion Our study shows promising clinical implications via faster pathology results by the RFU technique. This approach of calcium staining, though still in clinical trials, offers significant clinical application, allowing physicians to get the clinically diagnostic nerve injury degree faster and will also facilitate better strategies for further treatment or future surgeries.
Keywords: brachial plexus nerve injuries; peripheral nerve injury; relative fluorescence units; calcium nerve staining; grading peripheral nerve injuries